2011
DOI: 10.1136/sti.2010.046839
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with genitourinary medicine clinic attendance and sexually transmitted infection diagnosis among central and east European migrants in London

Abstract: CEE patients make up a notable minority of patients attending two central London GUM clinics. Higher numbers of sexual partners, homosexual partnerships and sexual mixing with people from outside the country of origin are associated with GUM clinic attendance. Heterosexual CEE men report behaviours associated with HIV/STI acquisition but appear to be underutilising GUM services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The subsequent full-text screening filtered out a further 50 publications to leave 23 articles. An editorial was excluded because it was not a research paper but this revealed three more studies [22][23][24] from a programme of work [25] on sexual risk-taking behaviour among Eastern European men that had already been included. Two other articles were also excluded as not being research papers.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent full-text screening filtered out a further 50 publications to leave 23 articles. An editorial was excluded because it was not a research paper but this revealed three more studies [22][23][24] from a programme of work [25] on sexual risk-taking behaviour among Eastern European men that had already been included. Two other articles were also excluded as not being research papers.…”
Section: Resultsmentioning
confidence: 99%
“…(StatSoft Inc., Tulsa, OK, USA, 2016) and R (R version 3.0.2) software [23]. Our main outcomes were risky sexual behaviors in the UK:

unprotected sexual contact with a casual partner,

sexual contact after the use of alcohol or recreational drugs,

having multiple sexual partners.

in the context of:

the pre- and post- migration comparison (a McNemar’s test was utilized for assessing any significant differences between two correlated proportions, based on the same sample of subjects, i.e., risky sexual behavior in Poland and in the UK).

variables influencing these outcomes while in the UK.

…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of the SALLEE (sexual attitudes and lifestyles of London's Eastern Europeans) project. Papers examining the sexual risk of CEE migrant men who have sex with men5 and CEE migrant attendance at genitourinary medicine clinics and STI diagnoses,6 which arise from this project as well, are also published in this issue of STI.…”
Section: Introductionmentioning
confidence: 99%